Figure 1 from: Zan ND, Sarbini A, Taha H, Tan IV, Azri A, Kahar R, Metali F, Ahmad N, Arai T (2020) Occurrence and ecological implication of a tropical anguillid eel, Anguilla marmorata, in Brunei Darussalam, Borneo Island. Zoologia 37: 1-7. https://doi.org/10.3897/zoologia.37.e39468 - Zan, Nur Dhabita; Sarbini, Ain; Taha, Hussein; Tan, Iy Vonne; Azri, Azie; Kahar, Rafhiah; Metali, Faizah; Ahmad, Norhayati; Arai, Takaomi (Zenodo, 2020)
Figure 1 Map showing the collection sites of a tropical anguillid eel Anguilla marmorata in Brunei Darussalam, Borneo Island and in the Bonin Islands, tropical islands of Japan. The location of the offshore spawning area of A. marmorata in North Pacific population (green ellipse) with the oceanic currents (blue lines) from the spawning area is shown. Black circles on the map indicate the sampling location.